Reviewing the Joint Patrol Policy in Government Regulation No. 13 Year 2022 and its Implications on the Authority to Maintain the Security of the East Java Regional Police Waters Area - pamungkas, rini; Hidayat, Heru Syamsul; Widayat, Yudhi (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
In order to implement efficiency, the government in 2022 has issued a policy in the form of Government Regulation Number 13 Year 2022 concerning the Implementation of Security, Safety and Law Enforcement in Indonesian Waters and Indonesian Jurisdictional Areas. The Joint Patrol Work Program as mandated by Government Regulation No. 13 Year 2022 is believed to be able to solve problems in the implementation of law enforcement, security and safety at sea in Indonesia is a “Single Agency Multi Tasks” system, with the Marine Security Agency as the leading sector. “.  In practice, for almost two years this joint patrol program has only selected priority areas while other areas have not been touched by this policy. The purpose of this study is to review the joint patrol policy, especially in the Water Police work area which until now has not been affected by the implementation of the policy as well as the East Java Water Police work area. With the empirical legal research method, the first research objective is to answer the perception of law enforcers after the enactment of Government Regulation No. 13 Year 2022 in the East Java Water Police working area, the second objective is to determine the strategy used to assess the new policy and its implications for the authority to maintain security and order in the waters of the East Java Regional Police. The results showed that law enforcement officers within the East Java Air Police have not yet understood the new policy. The results showed that law enforcement officials within the East Java Air Police did not understand the concept of Joint Patrols which was the obligation of the new policy, there was never any coordination with the Maritime Security Agency, The strategy that can be used to review and ensure the positive and negative impacts of the new policy is to use a Regulatory Impact Assessment study.